Expression and Secretion of Defined Cutinase Variants by Aspergillus awamori - van Gemeren, I. A. (American Society for Microbiology, 1998)
Several cutinase variants derived by molecular modelling and site-directed mutagenesis of a cutinase gene from Fusarium solani pisi are poorly secreted by Saccharomyces cerevisiae. The majority of these variants are successfully produced by the filamentous fungus Aspergillus awamori. However, the L51S and T179Y mutations caused reductions in the levels of extracellular production of two cutinase variants by A. awamori. Metabolic labelling studies were performed to analyze the bottleneck in enzyme production by the fungus in detail. These studies showed that because of the single L51S substitution, rapid extracellular degradation of cutinase occurred. The T179Y substitution did not result in enhanced sensitivity towards extracellular proteases. Presumably, the delay in the extracellular accumulation of this cutinase variant is caused by the enhanced hydrophobicity of the molecule. Overexpression of the A. awamori gene encoding the chaperone BiP in the cutinase-producing A. awamori strains had no significant effect on the secretion efficiency of the cutinases. A cutinase variant with the amino acid changes G28A, A85F, V184I, A185L, and L189F that was known to aggregate in the endoplasmic reticulum of S. cerevisiae, resulting in low extracellular protein levels, was successfully produced by A. awamori. An initial bottleneck in secretion occurred before or during translocation into the endoplasmic reticulum but was rapidly overcome by the fungus.